Karl Barth's concept of nothingness: a critical evaluation - Wallace, Layne (Peter Lang, 2020)
"Barth's Concept of Nothingness: A Critical Evaluation is an examination of Barth's discussion of the problem of evil in the Church Dogmatics. It provides a thorough exegesis of Barth's thinking on the origin of evil and the nature of the "shadow side" of creation in dialogue with John Hick and David Bentley Hart. The book's primary focus is in demonstrating the logical difficulties in Barth's thinking on the problem of evil. Further, it proposes a way forward that is beneficial to the pastor and provides hope and comfort to those in the midst of suffering and evil"--